Course and predictors of social security disability insurance in patients with borderline personality disorder over 24 years of prospective follow-up - Ueli Kramer; Christina M. Temes; Frances R. Frankenburg; Isabel V. Glass; Mary C. Zanarini (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Abstract Background The utilization of Social Security Disability Insurance (SSDI) is frequent in patients with borderline personality disorder (BPD) and may represent a meaningful marker of a patient’s symptom severity, poor psychosocial functioning, and/or inner suffering. Over 24 years of prospective follow-up, the present study aims to describe the course of SSDI and assess the role of clinically relevant predictors. Methods A total of 290 inpatients with BPD were interviewed at baseline and 12 consecutive follow-up waves, each separated by two years, after index hospitalization. Included were also 72 inpatients with other personality disorders. Surviving patients were reinterviewed. A series of interviews and self-report measures were used to assess psychosocial functioning and treatment history, axis I and II disorders, and childhood/adult adversity. Results Results show that rates of SSDI utilization were relatively stable over 24 years of follow-up (on average, 47.2% of the patients with BPD were on SSDI). Patients with BPD were three times more likely to be on SSDI than patients with other PDs. Patients with BPD displayed flexibility in their usage of SSDI. By 24 years, 46% of patients remitted, out of which 85% experienced recurrence and 50% of the patients had a new onset over time. In multivariate analyses, four variables were found to predict SSDI status in patients with BPD over time. These variables were: age 26 or older, lower IQ, severity of non-sexual childhood abuse, and presence of PTSD. Conclusions The results of this study suggest that a combination of a demographic factors, childhood adversity, natural endowment, and comorbidity are significant predictors of receiving SSDI over time. On a group level, there is a relative stability of SSDI usage over time, but on the individual level, the present study found a high fluctuation in receiving SSDI over 24 months of prospective follow-up.